Implementasi Metode Six Sigma dalam Pengendalian Kualitas Refined Bleached Deodorized Palm Oil di PT. ZZ: . - Aditya, Riski; Sundari, Susanti; Nudin, Burhan (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. ZZ is a company engaged in the processing of crude palm oil, often called Crude Palm Oil (CPO) and its derivatives. The production process in this company has two steps, namely the Refinery Plant and the Fractionation Plant. In the production process at the Refinery Plant, there is often a quality of Refined Bleached Deodorized Palm Oil (RBDPO) that does not comply with the qualifications determined by the company. The number of defective products will have an impact on the time and cost of production, which will increase. This study aims to determine and identify the causes of defective products in the production process using the six sigma method with the DMAIC approach so that it can be a proposal for improvement in the future. The results of this research are that the average sigma value obtained from January 2024 to April 2024 is 5.25, and the average DPMO value from January 2024 to April 2024 is 92.5. The sigma value shows a number that is close to the desired sigma target, namely 6, and based on Pareto diagram analysis, shows that the dominant defect is Free Fatty Acid (FFA). Keywords: CPO, DMAIC, Fractination Plant, RBDPO, Refinery Plant, Six Sigma